Civil Disobedience: Individual Liberty and Public Order - Kačerauskas, Tomas (Problemos, 2009)
Civil disobedience as a legal fight both for novelties in society and against the authority’s eccentric actions is analysed in the article. The first part is devoted to J. Rawls’ conception of civil disobedience in the perspective of his theory of justice. Rawls’ views are interpreted from the existential and historical approaches. Herewith are arisen the issues of an individual and a nation as his environment, of historical memory and the life plan to be created. Civil disobedience is interpreted as a public fight of an individual for his existential project in the worried society. According to the author, there is no exact coordinates of justice; they are changing during the interactions with our changing life project which covers the life plans of other participants of the community. There is suggested a bio-graphic approach to justice instead of the geo-graphic one, inasmuch as justice arises only in the light of an individual life plan while their light is thrown only in the space of particular society. Besides, justice under the influence of changing interaction between an individual and society is an alive phenomenon which is changing. The second part of the paper is devoted to the Confederation of Grand Duchy of Lithuania (1792–1793) as a case of civil disobedience. The following theses are presented: 1.1. The civil disobedience is a public political fight that expresses the freedom of individuals in a community both to change the social order and to consolidate the traditional moral attitudes. 1.2. Civil disobedience is a catalyst of society’s identity in the conditions of spiritual fight. 2.1. The deviation from justice has the drop effect. 2.2. A hardly noticed phenomenon of injustice could be a reason for overflowing of a cup, i.e. for civil disobedience which awakes revolutionary changes. 3.1. Nostalgia for unified society in order to assimilate the differences and to avoid spiritual fight is a chauvinistic attitude which impoverishes both the pluralistic society and an individual inside it. 3.2. Democratic aspirations (the rule of the majority) by ignoring the liberal attitudes lead to impoverishing the spiritual fight environment which matures an individual. 4. Our political freedom has been measured with a right to oppose the decisions that are contradictory to our principles as parts of the life plan.